Extraordinary Hispanic Americans - Alegre, Cesar, 1967- (New York : Children's Press, 2007)
The lives of some famous and accomplished Hispanic Americans
Includes bibliographical references (p. 275-277) and index
Keywords: Hispanic Americans -- Biography -- Juvenile literature; Hispanic Americans -- Biography